Exportações de petróleo e a maldição dos recursos naturais: um estudo empírico para o brasil - Ribeiro, Elaine Maria Fiuza (2019)
The Natural Resources Curse can be understood as a negative association between abundance of resources and economic growth. Some channels may be responsible for transmission that association, such as commodity prices, commodity price volatility, the insufficient manufacturing development, Dutch disease and the fragility of institutions. Several studies point out that the Curse is present mainly in oil-exporting countries, since the discovery of this commodity creates political problems and generates conflicts due to the fragility of the institutions, with the use of the revenues obtained for corruption. Therefore, the main objective of this dissertation is to verify if the increase in the oil exports share with the discovery of Pre-Salt in Brazil has had beneficial effects for the country between 2000 and 2017. The methodology used is the Autoregressive Models of Distributed Lagged Models (ARDL). The results suggest that there is a positive relationship between the level of Brazilian economic activity and oil exports in the long term, indicating that there is no evidence for the Natural Resources Curse. In addition, it can be seen that the institutional channel is an important variable, especially in a country that suffers from political issues and fragility of institutions, as ultimately evidenced by Operation Lava Jato.